2014
DOI: 10.1002/2014jd022076
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the respective roles of aerosols and clouds in the strong brightening since the early 2000s over the Iberian Peninsula

Abstract: The contribution of clouds and aerosols to the decadal variations of downward surface shortwave radiation (SSR) is a current controversial topic. This study proposes a method, which is based on surface-based SSR measurements, aerosol observations, and radiative transfer simulations (in cloud-free and cloud-and aerosol-free scenarios), to evaluate cloud-aerosol (CARE), cloud (CRE), and aerosol (ARE) radiative effects. This method is applied to quantify the role played by, separately, clouds and aerosols on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 74 publications
(71 reference statements)
7
52
2
4
Order By: Relevance
“…As was reported by Aas et al (2013), the particulate matter (PM) emissions in the Iberian Peninsula have decreased around 25 % between 2000 and 2011. Furthermore, observational PM data in different Spanish sites have also shown a decreasing trend in the 2000s (e.g., Barmpadimos et al, 2012;Cusack et al, 2012;Pey et al, 2013;Bennouna et al, 2014;Mateos et al, 2014). This fact can be understood by the effect of the current economic crisis and the implementation of new environmental laws to control the pollution (e.g., Querol et al, 2014).…”
Section: Analysis Of Aerosol Properties Over the Iberian Peninsulamentioning
confidence: 99%
“…As was reported by Aas et al (2013), the particulate matter (PM) emissions in the Iberian Peninsula have decreased around 25 % between 2000 and 2011. Furthermore, observational PM data in different Spanish sites have also shown a decreasing trend in the 2000s (e.g., Barmpadimos et al, 2012;Cusack et al, 2012;Pey et al, 2013;Bennouna et al, 2014;Mateos et al, 2014). This fact can be understood by the effect of the current economic crisis and the implementation of new environmental laws to control the pollution (e.g., Querol et al, 2014).…”
Section: Analysis Of Aerosol Properties Over the Iberian Peninsulamentioning
confidence: 99%
“…They found that cloudiness decrease appears to be the main driver for the 1990s-2000s brightening in Scandinavia, with likely additional contributions from decreasing aerosol concentrations. The relative contributions of cloud and aerosol effects may vary between Northern and Central Europe, although a strong cloudiness influence on SSR trends has also been found for the Iberian Peninsula [49]. Attribution of the differences in SSR trends and their drivers is a goal for future research, and one where satellite-based datasets such as CLARA and SARAH can play substantial roles.…”
Section: Assessment Of Ssr Trendsmentioning
confidence: 99%
“…In the context of Europe there have been a considerable number of regional studies that focus on trends in global radiation and their attribution, such as in Germany (Liepert and Tegen, 2002;Liepert and Kukla, 1997;, in Germany and Switzerland combined (Ruckstuhl et al, 2008;Ruckstuhl and Norris, 2009;Ruckstuhl et al, 2010), in Estonia (Russak, 2009), in the general Baltic states (Ohvril et al, 2009), in Spain (Mateos et al, 2014), in Norway (Parding et al, 2014), northern Europe in general (Stjern et al, 2009) and in Italy (Manara et al, 2015). Even though there are regional differences, the summarized global or allsky radiation data from Europe combined display a minimum in [1984][1985] at the end of a "dimming" period with a subsequent return to higher values.…”
Section: Introductionmentioning
confidence: 99%